The burden of cirrhosis and other chronic liver diseases due to hepatitis B in children and adolescents: results from global burden of disease study 2019 - Huang, Chenyang; Wu, Yaxin; Zhang, Chao; Ji, Dong; Wang, Fu-Sheng (Frontiers in Public Health, 2023)
The global burden of cirrhosis and other chronic liver diseases due to hepatitis B (collectively referred to as hepatitis B-associated cirrhosis in this paper) in children and adolescents must be understood and investigated.Methods: Data were extracted from the GBD database, and calculations were performed at global, regional, and national level. We calculate the incidence, prevalence, and disability-adjusted life years (DALYs) and annual average percentage changes (AAPCs).Findings: Globally, the prevalent cases of children and adolescents with hepatitis B-associated cirrhosis decreased from 125,053.98 × 10^3 in 1990 to 46,400.33 × 10^3 in 2019. Compared with 1990, the incidence rate of cirrhosis increased in low (95.51%) and low-middle SDI areas (26.47%), whereas it decreased in other SDI areas. The AAPC of incidence has increased in low-middle SDI areas (AAPC 0.12 [95% CI: 0.04-0.20]). At the regional level, the East Asia region has experienced the largest reduction. Conversely, Western Sub-Saharan Africa was the most serious region. Notably, South Asia was the only region where the AAPC of cirrhosis incidence (AAPC 0.77 [95% CI: 0.68-0.86]) increased. Conclusions: Globally, the overall burden of hepatitis B-associated cirrhosis in children and adolescents has declined significantly, but the number of cirrhosis incidence cases in low-middle and low-SDI areas has increased. The incidence in South Asia is rising, and the burden on Africa remains serious. Prevention and treatment of hepatitis B-associated cirrhosis in children and adolescents should not be ignored.